DNA‐Nanoparticle Tinkertoys. (15th April 2016) - Chandrasekaran, Arun Richard
Abstract: Nanoparticle superlattices can be self‐assembled by using DNA linkers, which gives control over their size, shape, and composition. Recently, such programmable atom equivalents have been tailored to respond to chemical stimuli and result in specific crystalline lattices. Moreover, the molecular recognition properties and the robustness of designed DNA nanostructures have been used in combination with metallic nanoparticles for the production of the elusive diamond superlattice. Abstract : Diamonds are DNA′s best friend : Programmable DNA strands have been used to assemble metallic nanoparticles into periodic lattices, including a diamond superlattice. Such DNA‐based interactions can be triggered using chemical cues, and have been used to control the lattice symmetry, composition, and properties of the crystals.